2005
DOI: 10.1212/01.wnl.0000171344.87802.94
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reproductive factors and postmenopausal hormone use on the risk of Parkinson disease

Abstract: Postmenopausal use of estrogen alone may increase the risk of Parkinson disease (PD) among women with a hysterectomy. Among women with natural menopause for whom the usual treatment is combined estrogen-progestin therapy, no increased risk of PD was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
5
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 26 publications
9
106
5
1
Order By: Relevance
“…In addition to epidemiologic studies, 1 experimental study also showed preliminary evidence that estrogen may abolish neuroprotection by caffeine among ovariectomized female mice (23). Nevertheless, a potential role of estrogen in PD etiology has yet to be defined, and the evidence to date on estrogen and PD has been inconsistent in both human studies (24,25) and animal experiments (26,27). Further, recent research suggests that the health implications of hormone use among women may depend on composition of the hormone preparation, time of initiation, duration of use, and type of administration (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epidemiologic studies, 1 experimental study also showed preliminary evidence that estrogen may abolish neuroprotection by caffeine among ovariectomized female mice (23). Nevertheless, a potential role of estrogen in PD etiology has yet to be defined, and the evidence to date on estrogen and PD has been inconsistent in both human studies (24,25) and animal experiments (26,27). Further, recent research suggests that the health implications of hormone use among women may depend on composition of the hormone preparation, time of initiation, duration of use, and type of administration (28).…”
Section: Discussionmentioning
confidence: 99%
“…40 However, other studies did or did not confirm these associations. 41,42 In the Mayo Clinic Cohort Study of Oophorectomy and Aging, women who underwent bilateral oophorectomy before the onset of menopause had an increased risk of parkinsonism compared with referent women (HR 1.80; 95% CI 1.00-3.26; P = 0.05), and the risk increased with younger age at oophorectomy (test for linear trend; P = 0.02). The findings were similar regardless of the indication for the oophorectomy (benign condition vs. prophylactic).…”
Section: Parkinsonism and Parkinson's Diseasementioning
confidence: 99%
“…When estrogen was administered either immediately after or 1 week after MA treatment, no evidence for neuroprotection was present [10, 11]. This study may provide an understanding of the variations in results on the effects of estrogen upon the NSDA neurodegenerative disorder, Parkinson’s disease, where positive [30,31,32,33,34,35,36], negative [34, 37] and no [30, 38, 39] effects of estrogen have been reported. The current model now provides a means to both understand and study these apparently contradictory effects.…”
Section: Discussionmentioning
confidence: 98%